STRATEGIC MANAGEMENT BASED ON LONGITUDINAL ACHIEVEMENT - Bali, Muhammad Mushfi El Iq; Khoiriyah, Fifin (STKIP Pesisir Selatan, 2025)
Quality education will be realized if the school implements the correct strategic management. Satisfying performance improvements are not only related to input and output aspects but also more important process aspects, namely, the teaching and learning process, monitoring and evaluation process, considering that the teaching and learning process has reached the highest level of importance compared to other processes. The method used in this research is qualitative research, where data collection techniques are through interviews, observation, and documentation. The results of this study indicate that the Nurul Barokah Islamic Boarding School has made significant progress. The management procedure goes according to a well-organized plan, in which management should start with effective and efficient Planning, Organizing, Actuating, and Controlling (POAC) to realize an increase in a good performance at the Nurul Barokah Islamic Boarding School. In this study, researchers attempted to analyze, understand, and describe the strategic management carried out at the Nurul Barokah Islamic Boarding School in improving the quality of Islamic boarding schools over a certain period (longitudinal achievement).